The experience of buprenorphine implant in patients with opioid use disorder: a series of narrative interviews - Scurti, Pietro; Nunzi, Marco; Leonardi, Claudio; Pierlorenzi, Claudio; Marenzi, Roberta; Lamartora, Vincenzo (Frontiers in Psychiatry, 2023)
Background This study used narrative medicine (NM) to assess the point of view of patients with opioid use disorder (OUD) and the impact that addiction and a new treatment approach via buprenorphine implant had on their daily lives as compared with previous oral Opioid Agonist Therapy (OAT). Methods Five patients with OUD undergoing treatment with a buprenorphine subcutaneous implant participated voluntarily and provided their anonymity by self-describing, in response to questions prompted by the clinician, their experience with this innovative therapy. The narratives were analyzed according to standard NM methodology. Citations of patients' positive or negative experiences with traditional OAT and buprenorphine implant were classified according to five categories—patient's determination toward complete opioid abstinence, emotional impact, impact on life, smoothness of therapy, and therapy dependency—and quantified to obtain a picture of the overall therapy experience. Results The analysis revealed the extent of the burden not only of addiction but also of the traditional OAT on patients' life, including relationships with family, job management, and free time. Conversely, the therapy with buprenorphine implant revealed a significant improvement in the quality of life of the patients, who also largely reported a positive emotional outcome during this therapy, as well as a solid determination to achieve complete recovery. Conclusions This study illustrates the complex problems of living with OUD and provides insights into the added value of an innovative buprenorphine implant therapy that, due to its administration route and prolonged duration, allows patients to take an additional step toward total opioid abstinence and complete recovery of daily life.